The construction of Professional Nursing Identity: a narrative literature review (Dissertation Nursing, 2024)
BACKGROUND: Professional identity is a construct that includes the personal, social and collective identity of a professional but is difficult to define. The nurse, in addition to encountering a difficult construction of his professional identity (IPI), is going through a strong moment of crisis, in which it emerges that a determining factor is precisely a weak IPI.PURPOSE: To summarize the knowledge relating to the nursing professional identification process, the crucial moments for its construction and the constituent elementsMATERIALS AND METHODS: A narrative literature review was carried out; PubMed, CINAHL, SCOPUS databases consulted with the following keywords: "nurse", "nurses", "nursing", "profession", "professional", "identity".RESULTS: 18 articles were included. IPI appears to be a constantly changing dynamic and flexible process . The nurse goes through fundamental moments in the construction of his IPI, implemented as his professional experience evolves. The factors involved in its construction are both intrinsic and extrinsic to the individual and the related outcomes can be both positive and negativeDISCUSSION: All the factors that emerged influence each other, thus also increasing the impact on the construction of the IPI and in some cases even the IPI itself impacts on certain factors. The individual elements involved in the construction of the IPI should be considered and analyzed more. A notable impact comes from social recognition which is still distorted and weak.CONCLUSIONS: The IPI is a dynamic construct to understand and analyzing the underlying processes can be useful, especially for the historical-evolutionary moment that the nursing profession is going through.